Pengaruh Putusan Mahkamah Konstitusi Nomor 25/PUU-XIV/2016 Terhadap Pemaknaan Pasal 4 UU Tipikor - Khoirul Ariwafa (Universitas Sains dan Teknologi Komputer, 2023)
This research aims to examine the influence of Constitutional Court Decision 25/2016 concerning the Meaning of Article 4 of Corruption Law. The research method uses literature and secondary materials. The research results concluded; First, the influence of the Constitutional Court Decision 25/2016 on Article 4 of the Corruption Law is interpreted as a material aspect so that the recovery of state financial losses can affect the non-fulfillment of the element of state financial losses which negates criminal responsibility for perpetrators of corruption. Second, the concept of recovering state losses in the perspective of microeconomic theory and restorative justice presents alternatives for solving corruption crimes. The alternative use of these settlements is considered effective and efficient in efforts to prevent the eradication of criminal acts of corruption and is in line with the establishment of the aim of the Corruption Law, namely saving state finances